‘Maze’ not pathway: focus group exploration of patients’ and public experiences of the UK NHS elective total joint arthroplasty pathway - Rosalind Raine; Naomi J Fulop; Helen Barratt; Jean Ledger; Raj Mehta; Sarah Jasim; Fiona Aspinal (BMJ Open)
Objective To explore patient and public perceptions of planned improvements to the National Health Service (NHS) total joint arthroplasty (TJA) pathway.Design Three qualitative focus groups undertaken March–May 2018, as part of a mixed-methods evaluation of Getting It Right First Time. Transcripts were subject to framework analysis to identify thematic content between October 2018 and October 2021.Setting Elective TJA surgery in the English NHS.Participants Two focus groups including patients who had undergone TJA in the previous 2 years (group 1: n=5; group 2: n=4) and the other individuals who had not but were aged 60+ (group 3: n=5). Participants were recruited via community groups and patient panels.Results Fourteen individuals took part in the focus groups; all were aged over 60; seven (50%) were female and nine (64%) had undergone TJA surgery. Participants’ perspectives were categorised into themes and mapped onto stages of the TJA pathway. Although perioperative care is often the focus of improvement efforts, participants argued that the patient journey begins before individuals present to primary care. Participants had concerns about other aspects of the pathway, such as obtaining a surgical referral, with prereferral interventions aimed at potentially avoiding the need for surgery (ie, physiotherapy) being perceived as a mechanism to restrict access to secondary care. Patient experience was also conceptualised as a ‘maze’, rather than the logical, sequential process set out in clinical guidelines; exacerbated by a lack of information, knowledge and power imbalances.Conclusion The linear conceptualisation of the TJA pathway is at odds with patient experience. Improvement programmes focused on perioperative care fail to consider patient concerns and priorities. Patients should be directly involved in improvement programmes, to ensure that patient experience is optimised, as well as informing related processes and important outcomes of care.